PENERAPAN MODEL PEMBELAJARAN MENCARI PASANGAN DAN BERTUKAR PASANGAN DALAM KELOMPOK DISKUSI TERHADAP HASIL BELAJAR SISWA PADA MATERI SISTEM KOLOID KELAS XI IPA MAN 1 KOTA BENGKULU - Sella Aprianika; Amrul Bahar; Salastri Rohiat (University of Bengkulu, 2019)
This study aims to determine differences in student learning outcomes using a model of learning make a match with a model partner switch the subject matter colloidal system class XI IPA MAN 1 Bengkulu City in the academic year 2017/2018. The research population of all classes XI IPA amounted to 4 classes with a total population of 151 students. The sampling of the research was done by normality test and homogeneity test before the study population. Obtained a sample of research that consists of 2 classes of class XI IPA 1 as an experimental class I that apply the model make a match and class XI IPA 2 as an experimental class II using a model parten switch. Student learning outcomes are seen from the postest score. Students' learning outcomes in the make a match class had an average of 82.714 while in the partner switch the average pair was 77.5. This shows that the model of make a match is more effectively used in the process of learning in class than the model of partner switch. From the t test-t test on both experiment classes is obtained tcount and ttable = 1.707> 1.666 (? = 0,05). The results show that H0 is rejected and Ha is accepted which means that there is a significant difference between the learning result of the students using make a match model and the learning model partner switch on the material of the colloidal system.